Dietary choline intake and colorectal cancer: a cross-sectional study of 2005–2018 NHANES cycles - Xu, Xijuan; Ying, Hongan; Huang, Lili; Hong, Weiwen; Chen, Wenbin (Frontiers in Nutrition, 2024)
Background: It remains unclear if choline intake is associated with colorectal cancer. Therefore, we examined data from the National Health and Nutrition Examination Survey (NHANES).This cross-sectional study included 32,222 U.S. adults in the 2005-2018 NHANE cycles, among whom 227 reported colorectal cancer. Dietary choline was derived from 24-hour recalls. Logistic regression estimated odds of colorectal cancer across increasing intake levels, adjusting for potential confounders.Results: After adjusting for sociodemographic variables, BMI, alcohol use, smoking status, comorbidities, and dietary factors (energy, fat, fiber, and cholesterol), the odds ratio (OR) for colorectal cancer was 0.86 (95% CI: 0.69-1.06, P=0.162) per 100 mg higher choline intake.Across increasing quartiles of choline intake, a non-significant inverse trend was observed (Q4 vs Q1 OR: 0.76, 95%CI: 0.37~1.55, P-trend= 0.23). Subgroup analyses revealed largely consistent associations, with a significant interaction by hypertension status (P-interaction =0.022).In this large, nationally representative sample of U.S. adults, higher dietary choline intake was not significantly associated with colorectal cancer odds after adjusting for potential confounders. However, a non-significant inverse trend was observed. Further prospective studies are needed to confirm these findings and elucidate the underlying mechanisms.